Vertical distribution of weed seed bank in three-year-old oil palm plantations - LENTINA SITINJAK; EDISON PURBA; CHAIRANI HANUM; LUTHFI AZIZ MAHMUD SIREGAR (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Sitinjak L, Purba E, Hanum C, Siregar LAM. 2025. Vertical distribution of weed seed bank in three-year-old oil palm plantations. Biodiversitas 26: 3571-3579. Soil may contain millions of weed seeds from different species. Understanding the soil seed bank is crucial for making effective and sustainable weed management plans. This study provides novel insight into vertical seed bank distribution in tropical agroecosystems, a topic that remains underexplored, so that it can prevent reinfestation and dependence on herbicides. In this study, we measured the species composition and vertical distribution of the weed seed bank in agricultural soil. We collected soil samples using a 9 cm diameter soil core in a zigzag pattern. Samples were taken at depths of 0-5 cm, 5-10 cm, 10-15 cm, and 15-20 cm, with four duplicates per depth. At Universitas Sumatera Utara, Indonesia, each sample was spread in sterile trays filled with sand and incubated in a greenhouse. Seedling emergence was monitored for eight weeks. No new seedlings appeared in the last two weeks. A vegetation survey at the sampling site was also included. Data were analyzed using a non-factorial, randomized complete block design. Seedling emergence was significantly affected by soil depth. The highest seed bank density was at 5-10 cm (51.50 seedlings, 43.45%), followed by 0-5 cm (48.75 seedlings, 41.14%), 10-15 cm (12.50 seedlings, 10.55%), and 15-20 cm (5.75 seedlings, 4.85%). In total, the seed bank produced 354 seedlings. Asystasia gangetica was the most common, with 131 individuals. Aboveground vegetation yielded 256 individuals, predominantly Persicaria odorata (38 individuals, 14.84%). Most weed propagules accumulated in the top 10 cm of soil. Thus, shallow tillage, competitive cover crops, and well-timed herbicide applications targeting seedling flushes should focus on this layer. To prevent replenishment of the seed bank and curb invasive or resistant species, seasonal adjustments and routine observation of the seed bank and vegetation are vital. This integrated, site-specific approach supports more effective and sustainable weed control in agricultural systems.